2001
DOI: 10.1099/00221287-147-10-2783
|View full text |Cite
|
Sign up to set email alerts
|

Fluoranthene metabolism in Mycobacterium sp. strain KR20: identity of pathway intermediates during degradation and growth

Abstract: Mycobacterium sp. strain KR20, which was isolated from a polycyclic aromatic hydrocarbon (PAH) contaminated soil of a former gaswork plant site, metabolized about 60 % of the fluoranthene added (05 mg ml N1 ) to batch cultures in mineral salts medium within 10 d at 20 mC. It thereby increased its cell number about 30-fold and produced at least seven metabolites. Five metabolites, namely cis-2,3-fluoranthene dihydrodiol, Z-9-carboxymethylenefluorene-1-carboxylic acid, cis-1,9a-dihydroxy-1-hydro-fluorene-9-one-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
59
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 46 publications
7
59
0
2
Order By: Relevance
“…5D). HPLC and UV spectral analysis indicated that this metabolite had a UV absorption spectrum similar to that reported for fluoranthene cis-2,3-dihydrodiol (52). As shown in Table 2, we also detected compounds whose mass spectra were similar to those of monohydroxyfluoranthene ([M ϩ ·] at m/z 290) and fluoranthenediols ([M ϩ ·] at m/z 378) which we considered to be derived from dehydration of fluoranthene cis-dihydrodiol.…”
Section: Resultsmentioning
confidence: 51%
“…5D). HPLC and UV spectral analysis indicated that this metabolite had a UV absorption spectrum similar to that reported for fluoranthene cis-2,3-dihydrodiol (52). As shown in Table 2, we also detected compounds whose mass spectra were similar to those of monohydroxyfluoranthene ([M ϩ ·] at m/z 290) and fluoranthenediols ([M ϩ ·] at m/z 378) which we considered to be derived from dehydration of fluoranthene cis-dihydrodiol.…”
Section: Resultsmentioning
confidence: 51%
“…5,6-Benzocoumarin was reported earlier as one of the compounds produced from phenanthrene-1,2-dihydrodiol (Pinyakong et al, 2000). Although the intradiol cleavage of highmolecular-mass PAH diols is usually limited to K-region diols (Rehmann et al, 1998;Vila et al, 2001), there are reports on intradiol cleavage of the non-K region diol of PAHs (Dean-Ross et al, 2001;Rehmann et al, 2001;Keum et al, 2006;Kim et al, 2005;Lopez et al, 2006). Naphthalene-1,2-dicarboxylic acid identified in this study was found to be a dead-end metabolite and was not degraded further by strain PN/Y.…”
Section: Discussionmentioning
confidence: 99%
“…In the short time since these reviews appeared, more examples of novel metabolic pathways and cooxidation products have been described. For example, Rehmann et al (507) outlined a new pathway for fluoranthene metabolism in Mycobacterium sp. strain KR20, whereby initial dioxygenation commences at the 2,3 position (Fig.…”
Section: Aerobic Pah Metabolismmentioning
confidence: 99%